The Use of Human Factor Approach in the Study of Connectivity between Organizational Training and Workplace Practice Using Chinhoyi University of Technology Employees’ Perceptions as a Case Study (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2012)
The purpose of the study was to explore the perceptions of Chinhoyi Universityof Technology employees about the possibility of using the Human Factor approach as atool of analysis in enhancing connectivity between organizational training and workplacepractice through inculcation of positive attitudinal and behavioral change among its staff.The research adopted a quasi – qualitative approach allowing for triangulation of data. Datawere collected through questionnaires for lower grades and interviews for heads of section.Stratified sampling was employed to select 109 respondents who filled in the selfcompletion questionnaires which were analyzed using the social packages for socialscientists (SPSS). Eleven heads of sections were interviewed and the recorded data wereanalyzed using a descriptive thematic generation approach. The research findings revealthat employees are aware of the negative Human Factor issues that affected organizationalculture and behavioral norms, an element which was said to be working againstorganizational effectiveness within the university‟s service structure and departments. Lackof good work ethics, „hunhuism‟ and absence of induction was identified as a major criticalcomponent characterizing the negative workplace practice. Additionally the studyhighlights cases of human factor decay as evidenced by dismissal of perpetrators. Thus, thestudy recommends the provision of relevant training programmes as part of Human Factordevelopment thrust through prioritization of training programmes aimed at inculcating thecorrect human factor characteristics in employees
Keywords: organizational culture, behavioural norms, induction, workplace practice